2005
DOI: 10.1590/s1519-566x2005000500021
|View full text |Cite
|
Sign up to set email alerts
|

Calliphoridae (Diptera) coletados em cadáveres humanos no Rio Grande do Norte

Abstract: -This paper reports a study on Calliphoridae associated to human corpus in Rio

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 3 publications
0
10
0
4
Order By: Relevance
“…Therefore, the present study observed that the duration of immature stage development period of N. vitripennis Table 3 Mean of parasitoids emerged per pupa in treatments where one pupa was exposed to different numbers of female parasitoids (1:1, 1:3, 1:5, 1:7, 1:9, 1:11) Mean values followed by the same letter do not differ significantly at the 5% level according to Tukey's HSD under controlled temperature and relative humidity, using different quantitative associations of hosts and parasitoids, may cause variations in the duration of the immature stage development period of parasitoids. Thus, these results are extremely important, since in natural conditions, the C. megacephala are an important forensic indicator and usually one of the first species to arrive and lay eggs on the carcasses (Andrade et al 2005). Moreover, C. megacephala species are naturally parasitized by N. vitripennis (Carvalho et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the present study observed that the duration of immature stage development period of N. vitripennis Table 3 Mean of parasitoids emerged per pupa in treatments where one pupa was exposed to different numbers of female parasitoids (1:1, 1:3, 1:5, 1:7, 1:9, 1:11) Mean values followed by the same letter do not differ significantly at the 5% level according to Tukey's HSD under controlled temperature and relative humidity, using different quantitative associations of hosts and parasitoids, may cause variations in the duration of the immature stage development period of parasitoids. Thus, these results are extremely important, since in natural conditions, the C. megacephala are an important forensic indicator and usually one of the first species to arrive and lay eggs on the carcasses (Andrade et al 2005). Moreover, C. megacephala species are naturally parasitized by N. vitripennis (Carvalho et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, Oliveira-Costa et al (2001b) found this species of blowfly colonising human corpses in Rio de Janeiro. Andrade et al (2005) also collected maggots of this species in the decay stage in human corpses. However, according to Souza and Linhares (1997), this species could not be fundamentally necrophagous because collected few individuals on pig carcasses in Campinas, state of São Paulo (SP).…”
Section: Relation Between Coloniser Species Vs Decomposition Stages -mentioning
confidence: 99%
“…Em experimento realizado com carcaças de porcos no sul de Goiás a espécie apareceu como a mais abundante representando 89,4% da fauna cadavérica 10 . Já em coletas realizadas em cadáveres humanos no Rio Grande do Norte, C. albiceps se apresentou como a segunda espécie em número de indivíduos 11 . Na região de Campinas, estado de São Paulo, experimentos com carcaças de porcos expostas em áreas urbanas apresentaram C. albiceps como espécie significativa da fauna regional 12 .…”
Section: Descritoresunclassified